Feminisms: a study about contemporary narratives of the feminine and the social network - Oliveira, Paula Gorini (Revista Hipótese, 2016)
The present paper is about contemporary narratives of feminism. Inspired on the Actor-Network Theory and in the method of cartography, it aims to map the production of subjectivity from the perspective of a participant observation. It debates the production of affections and the dispute narratives at social networks, as well as the concept of “presence production”, from Gumbrecht, in the debate between the body and its virtuality. This work is not concerned about the results, but with crossing data and raising of questions.
Keywords: Feminism; Communication; Social Network; Production of affections